Discontinuation of thyroid hormone treatment among children in the United States with congenital hypothyroidism: findings from health insurance claims data - Grosse Scott D; Ouyang Lijing; Kemper Alex R (BMC, 2010)
Abstract Background Thyroid hormone treatment in children with congenital hypothyroidism can prevent intellectual disability. Guidelines recommend that children diagnosed with congenital hypothyroidism through newborn screening remain on treatment to at least 3 years of age, after which a trial off therapy can determine which children have transient hypothyroidism. The purpose of this study was to describe the rate at which children with congenital hypothyroidism in the United States discontinue thyroid hormone treatment in early childhood. Methods Retrospective analysis of the 2002-2006 MarketScan® Commercial Claims and Encounters research databases and the 2001-2005 MarketScan Multi-State Medicaid databases. Children were classified as having congenital hypothyroidism based on billing codes and having filled a prescription for thyroid hormone treatment. Kaplan-Meier curve analysis was used to determine discontinuation rates. Results There were a total of 412 Medicaid-enrolled children and 292 privately-insured children with presumed congenital hypothyroidism included in this study. The overall birth prevalence of congenital hypothyroidism across both datasets was about 1 per 2,300. By 36 months, the percentage who had discontinued thyroid replacement treatment was 38% (95% Confidence Interval: 32%-44%). Medicaid-enrolled children had a more rapid decline in the first 24 months of treatment compared to those with private insurance (P = 0.02). Conclusions More than one-third of children treated for congenital hypothyroidism discontinued treatment within 36 months, which is inconsistent with current guidelines. It is not known how many of these children required continued treatment or experience adverse effects from discontinuation. These findings emphasize the critical need for follow-up systems to monitor the outcome of newborn screening.